PERUBAHAN SISTEM PENDIDIKAN ISLAM DI IRAK - Nova Riza; Ria Rachmawati (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
The success of this Islamic educational institution is connected and linked to the history of its predecessors who have been involved in every aspect of human life, both sociologically, which responds to social problems and psychologically, which responds to all forms of human (soul/spirit) complaints. The success that has been achieved in this educational institution cannot be separated from the system that applies within it, including the goal of the Hauzah itself, by producing Mujtahids and then preparing them to become preachers and preachers to carry out the tabligh's mandate. It is also inseparable from the activities of the students who not only study theoretical knowledge in the form of understanding, but also practice what they have learned in the form of Islamic morals/ethics and spirituality such as prayer, fasting, celebrating Islamic holidays and so on. One of the breakthrough forces in Hauzah is Intellectual and Spiritual. It is one of the pillars of civilization in Iraq and Iran, because it is not affected by the political turmoil that occurred there and is more focused on scientific demands, so that the purity of this Islamic institution is well maintained.